2015
DOI: 10.1007/s10482-015-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lactobacillus reuteri in infantile colic and colicky induced maternal depression: a prospective single blind randomized trial

Abstract: Infant colic, excessive crying of unknown cause, is a major burden to families and effects about 10-30 % of infants. Despite decades of research, the exact cause and treatment of infant colic has remained elusive. The use of Lactobacillus reuteri (DSM 17938) in infant colic is somewhat controversial and hence, we designed this study to evaluate its efficacy in infantile colic. We recruited predominantly or exclusively breastfed infants, aged less than 4 months in a placebo controlled observational randomized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 13 publications
3
81
0
7
Order By: Relevance
“…The characteristics of the seven included RCTs [915] that recruited a total of 471 infants are summarized in Table I. With one exception [13], all trials were double-blind and placebo controlled. All RCTs were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the seven included RCTs [915] that recruited a total of 471 infants are summarized in Table I. With one exception [13], all trials were double-blind and placebo controlled. All RCTs were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Five included RCTs involving 349 infants assessed the effect of administration of L. reuteri DSM 17938 at a daily dose of 10 8 colony forming units (CFU) given for 21 days [9, 10, 12, 13] or 28 days [11]. Four RCTs involved only infants with infantile colic who were breastfed exclusively or predominantly [9, 10, 12 13], and one RCT involved both breastfed and formula-fed infants [11].…”
Section: Resultsmentioning
confidence: 99%
“…Several small studies in predominantly breast-fed colicky infants have consistently reported a significant effect on infant colic vs. controls [37][38][39][40] and, according to meta-analysis, the effects were most evident after 21 days of supplementation [41]. However, a randomized study on a larger population including both breastfed and formula-fed colicky infants reported conflicting results, due to a lack of significant difference in responder rate in the overall population (P=0.23), and a significant increase in crying and especially fussing in the subgroup of formula-fed infants (79 minutes on average, P=0.005) [42,43].…”
Section: Bfmentioning
confidence: 99%
“…ise yaptıkları çalışmada, probiyotiklerin (Lactobacillus reuteria) kolikli bebeklerin ağlama sürelerini anlamlı dü-zeyde düşürdüğünü göstermişlerdir. 17,61 Markestad yaptığı çalışmada, kolikli bebeklerin tedavisinde sükroz solüsyonunun plaseboya göre daha etkili bir yöntem olduğunu göstermiştir. 13,62 Huhtala ve ark.…”
Section: Di̇ğer Tedavi̇ Yöntemleri̇unclassified
“…12 Diğer tedavi yöntemleri arasında probiyotik kullanımı ve akupunktur gibi uygulamalar sayılabilir. [13][14][15][16][17] İnfantil koliğe hemşire yaklaşımı ise ailenin yaşadığı stresle baş etmesi için desteklenmeli, öz-güvenini artırıcı yöntemler denenmeli, koliğin sü-resini ve şiddetini azaltıcı tedavi yöntemleri aileye öğretilmelidir. 18 Bunun yanı sıra aileye davranış tedavisinde bebeğe daha az uyaran verilmesinin gerekliliği de öğretilmelidir.…”
unclassified